RADIATION SAFETY JUSTIFICATION FOR THE LONG-TERM STORAGE OF GAS CONDENSATE IN THE UNDERGROUND RESERVOURS FORMED BY THE NUCLEAR EXPLOSION TECHNOLOGY - I. K. Romanovich; S. L. Speshilov; M. K. Teplov (Радиационная гигиена)
The paper presents approaches to the safety justification of the gas condensate and brine long-term storage in the underground reservoirs formed by the nuclear explosion technology. Gas condensate and brine are the intermediate level liquid radioactive waste containing isotopes: 3Н, 137Cs and 90Sr, in traces - 239Pu, 235U, 241Am.Safety of the gas condensate and brine long-term storage in the underground reservoirs is assessed on the base of the multi-barrier principle implementation, used during radioactive waste disposal. It is shown that the gas condensate and brine long-term storage in the sealed underground reservoirs formed by nuclear explosion technologies in salt domes does not lead to the surface radioactive contamination and population exposure.